Innovating organization and management : new sources of competitive advantage - Foss, Nicolai J., 1964- (Cambridge ; New York : Cambridge University Press, 2012)
"The search for competitive advantage serves as the basis for organizational strategy. This book argues that there are four key sources of competitive advantage and financial success that have not been given the attention they deserve. Firstly, that organizational design and management processes may be strategic resources in their own right. Secondly, that organizational design and management processes can be deployed to create new strategic resources. Thirdly, that managers have begun to think of organizational design and management processes in a proactive way rather than seeing them more passively as necessary facilitators of success. Fourthly, that this new way of looking at organization and management requires a search for new ways of structuring organizational design and managerial processes. These points are driven home through case studies of the Danish firms LEGO Group, Vestas Wind Systems, Coloplast, Chr. Hansen, IC Companys and NKT Flexibles"--
"The dominant thinking in strategic management stresses the importance of assets, such as reputation, intellectual property rights, and relations with suppliers and customers. Less attention has been dedicated to organizational design and new management processes. However, the above discussion highlights the fact that such designs and processes can serve as strategic resources for firms. In other words, if they are properly organized and deployed, such resources can contribute decisively to corporate success. Thus, they contribute to the value the company can create and the value it can appropriate. They also help to make sure that the focal firm's level of appropriated value is higher than that of the competition. As mentioned above, management academics have only recently begun to put their academic talents to use in the analysis of management innovation. Therefore, the ways in which management innovations and improvements in organization and management processes can contribute to competitive advantage are far from fully understood"--
Machine generated contents note: List of figures; List of tables; List of boxes; 1. New sources of competitive advantage; 2. Causes of firm success: from resources to organization and management; 3. LEGO: redefining the boundaries; 4. Vestas: the will to win(d); 5. Coloplast: innovating innovation; 6. Chr. Hansen: collaborative forms under private equity ownership; 7. IC Companys: creative genius and commercial attitudes; 8. NKT Flexibles: global sourcing of R and D innovation; 9. Concluding reflections: innovating organization and management to stay competitive; Index.
Includes bibliographical references and index.
Keywords: Organizational effectiveness; Strategic planning; Management; Success in business; BUSINESS & ECONOMICS / Strategic Planning